Examining the Examinations
320 p.
Keywords: Examining the Examinations looks at the required advanced science and mathematics examinations taken by university-bound students in seven countries. This research focuses on topics covered, types of questions used, and performance expected from students. The book concentrates on comparisons of the examinations, illustrating their similarities and differences with selected questions taken from the actual examinations. The international comparisons presented offer a window on educational `laboratories' in seven countries.